If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(u-3)(u+6)=
We move all terms to the left:
(u-3)(u+6)-()=0
We add all the numbers together, and all the variables
(u-3)(u+6)=0
We multiply parentheses ..
(+u^2+6u-3u-18)=0
We get rid of parentheses
u^2+6u-3u-18=0
We add all the numbers together, and all the variables
u^2+3u-18=0
a = 1; b = 3; c = -18;
Δ = b2-4ac
Δ = 32-4·1·(-18)
Δ = 81
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:u_{1}=\frac{-b-\sqrt{\Delta}}{2a}u_{2}=\frac{-b+\sqrt{\Delta}}{2a}\sqrt{\Delta}=\sqrt{81}=9u_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(3)-9}{2*1}=\frac{-12}{2} =-6u_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(3)+9}{2*1}=\frac{6}{2} =3
| -4p-3(5-3p)=2(p-3)-18 | | 7w+3=104/2 | | 4x+2(5-6x)=x+28 | | 4x-2-2(x-9)-6(x-5)=55-6x-21 | | 6x=12 | | 3(e-2)=2(4e+5)+e | | 2(-8x+4)+3=-16x+14 | | 4+3a+5=0 | | 2+4(5-2x)=3(x-12)-8 | | 3(1-7x)=24 | | 2/3x+8=-7 | | 4x-4=5x12 | | -4x-24=-12 | | t(-5)=9 | | T=15c+60(8-c) | | -6=-6-n | | x/7+11=-10.1 | | 1+k=-11+7k | | 5x-12=-4x+55 | | 6(3x+1)+2(3x-5)=20 | | 3x-8(2x+7)=14-3(2x+1) | | -10=-(x-7) | | 7=27-4x | | –7x=91 | | x+4(3/2)=14 | | 3.–7x=91 | | z/31=-29 | | 2(3x+2)+2(5x+4)+5=16x+17 | | 5x+4-2x+1=5(x-1)-2 | | 5/7p-2/6p+12=6 | | /7x^{-1}=/49x^{x-1} | | 2x-7=-3+23 |